Tramas tróficas de peces de arrecifes en la región noroccidental de Cuba. II. Grupos funcionales - Hernández, Ivet (2008)
A conceptual model of the food webs, mainly with fish, was built in a rocky shore of Havana City with data covering from October 2004 to February 2006. The stomach contents of the most abundant fish was complemented with the literature. We used the Relative Importance Index method to describe diets of carnivorous and omnivorous fish; and a modification of the Relative Abundance method for sponge eaters and herbivorous fish. Agglomerative numeric classification techniques were used to determine the diet’s similarity. The matrix was made using Bray-Curtis dissimilarity index. Ten functional trophic groups were formed on the basis of diet similarity. The cascade effect is evidenced in this area by the big top predator shortage and the dominance of a few low trophic level species. The regulator role of top predators is low because of over-fishing: the trophic web of this area is highly altered.